KUALITAS PELAYANAN KEPESERTAAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN PESERTA PEKERJA BUKAN PENERIMA UPAH (PBPU) DI KABUPATEN BATANG - Novia Cesar Muhgni Putri; Susilo Utomo; Lusia Astrika (Journal of Politic and Government Studies, 2015)
AbstractAssesment of the public services quality is conducted to determine the gains of the service unit of BPJS Health Care Office in Batang. BPJS Health Care is expected to bring positive impacts for ensuring public health. However, there is a problem that the quality of services sometimes does not serve customers’ expectation, which means that there is still lack of satisfaction with the services performed. This study aimed to examine the quality of BPJS Health Care participant services in Batang using five public service factors of SERVQUAL, Realibility, Responsiveness, Assurance, Empathy, and Tangibles.By using the theory of service quality (SERVQUAL) and then processed using data processing methods set out in KEPMENPAN number 25 of 2004 on the General Guidelines for Preparation of Public Satisfaction Index (HPI) using the 15 service elements to assess the quality of BPJS Health Care participant services in Batang. Respondents in this study were participants of BPJS Health Care in Batang which in class of Workers Not Wage Receivers or Independent Workers, a total of 100 respondents were used as samples.The results showed the public's assessment of the quality of BPJS Health Care participant services in Batang rated Good. From the data that has been processed, the value of SMEs to quality of service was 77 which refers to a category B or Good. However, from the study conducted there are still several things that need to be improved. From the 5 factors of service quality and 15 service elements there are some elements that still need improvement from BPJS Health Care Batang in order to achieve grade A or Very Good .The study recommends, a good service quality should be the top priority in doing services in order to achieve the satisfaction of BPJS Health Care customers in Batang.Keywords: Quality of Service; Public Satisfaction; BPJS Health Care